No association between CYP2C19 genetic polymorphism with treatment remission to antidepressant venlafaxine in Han Chinese population. (February 2020) - Zhang, Naixing; Ji, Lei; Chen, Zhixuan; An, Lin; Ren, Decheng; Bi, Yan; Guo, Zhenming; Yuan, Ruixue; Yuan, Fan; Dong, Zaiquan; Yin, Li; Sun, Xueli; et al.
Abstract : Objective: Major depressive disorder (MDD) is a global mental health problem. As a serotonin-noradrenaline reuptake inhibitor (SNRI), the antidepressant venlafaxine is used to alleviate MDD clinically. Recent research has shown that Cytochrome P450 (CYP) enzymes affect venlafaxine efficacy by mediating its metabolism. The present study investigates genetic polymorphisms of cytochrome P450 family 2 subfamily C member 19 (CYP2C19) are associated with remission after venlafaxine treatment for MDD. Methods: A total of 175 Han Chinese patients with depression were recruited to accept a 6-week treatment with venlafaxine. Three single-nucleotide polymorphisms of CYP2C19 were selected from dbSNP and previous literature to compare the allele and genotype frequencies between patients in remission and nonremission. Seventeen items Hamilton Depression Scale (17-HAMD) was used to access the outcomes of patients' depressive symptoms through the study. Our results denied the role of CYP2C19 polymorphisms for remission after venlafaxine treatment in MDD patients. Result & Conclusion: CYP2C19 genetic polymorphism may not have association with SNRI venlafaxine treatment remission in the Han Chinese population.